Delayed hypoxic encephalopathy: a rare complication of methadone poisoning in two cases - Abdollahifard, Saeed; Kheshti, Fatemeh; Inaloo, Soroor (Iranian Journal of Child Neurology, 2022)
Methadone is a kind of opioid that is used to reduce the pain of addicts who decide to withdraw drugs. Sometimes due to a lack of appropriate cautions, this drug will be accessible to children, andpoisoning might occur. Methadone poisoning usually presents with the loss of consciousness and pinpoint pupils. Herein, we present two cases of delayed hypoxic encephalopathy that had been poisoned by methadone